2017
DOI: 10.1016/j.amjcard.2016.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Calcium Scoring as a Screening Examination in Patients With a History of Kawasaki Disease

Abstract: Subsets of patients with a remote history of Kawasaki disease (KD) have coronary artery aneurysms with associated risks of late morbidity. In a pilot study we previously showed that computed tomography (CT) coronary artery calcium (CAC) scoring detects late CAC in patients with aneurysms and a remote history of KD. We performed CT calcium volume scoring in 166 subjects (median age 19.5 years) with a remote history of KD (median interval from KD to CT 15.1 years). Coronary arteries were classified as normal (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Coronary CT angiography is a sensitive noninvasive test to evaluate older patients for Kawasaki disease-associated coronary abnormalities (Fig 14). Interestingly, low-attenuation lesions that mimic noncalcified atherosclerotic plaque may also be observed (53). The coarse calcifications often described within the coronary arteries of patients with Kawasaki disease is a later finding, usually evident years after the acute phase and rarely seen without underlying CAAs (53) (Fig 15).…”
Section: Vasculitis Kawasaki Diseasementioning
confidence: 99%
“…Coronary CT angiography is a sensitive noninvasive test to evaluate older patients for Kawasaki disease-associated coronary abnormalities (Fig 14). Interestingly, low-attenuation lesions that mimic noncalcified atherosclerotic plaque may also be observed (53). The coarse calcifications often described within the coronary arteries of patients with Kawasaki disease is a later finding, usually evident years after the acute phase and rarely seen without underlying CAAs (53) (Fig 15).…”
Section: Vasculitis Kawasaki Diseasementioning
confidence: 99%
“…Blood calcium changes in KD patients have not been discussed frequently before. Andrew M. Kahn and his colleagues reported that coronary artery calcium scoring had a good performance in detecting coronary artery abnormalities in KD patients [ 33 ], but the relationship between coronary artery calcium scoring and blood calcium is still uncertain [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcium scoring may be a useful tool to screen patients with a remote history of Kawasaki disease or unknown coronary artery status such as probable Kawasaki disease. 9 We reported that the larger coronary artery diameter caused by Kawasaki disease, resulted in an earlier appearance of coronary artery calcifications in the coronary artery lesions. 10 The timing of the appearance of coronary artery calcifications between the giant aneurysms and medium aneurysms differed.…”
Section: Discussionmentioning
confidence: 94%